Impact of Tiktok on the generation of engagement in fashion brands: Analysis of Zara's profile - Ruíz Viñals, Carmen; Pretel, Marilé; del Olmo Arriaga, José Luís (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2024)
TikTok, with its visual content and configuration, has emerged as a powerful platform for fast fashion. The study examines how Zara uses TikTok to communicate with consumers, promote products and strengthen its brand. Content strategies, interaction with users and the impact on brand perception have been analyzed. It has been observed that collaborations with content creators and special launches expand the audience and generate greater engagement. Video length also influences success, with an inverse correlation between length and "likes". This analysis provides insights to understand and optimize brand presence on TikTok.